Emotional labor and job satisfaction among nurses: The mediating effect of nurse–patient relationship - Xu, Yi-wei; Fan, Ling (Frontiers in Psychology, 2023)
Emotional labor is considered an important part of the role in the nursing field. Previous studies have found inconsistencies between emotional labor and job satisfaction of nurses, this is due to the relationship between them being affected by other factors. However, the current nurse-patient relationship is tense and leads to an unsafe and unstable working environment for nurses. It has yet to be confirmed whether the nurse-patient relationship can be used as a mediating variable to further explain the association that exists between emotional labor and job satisfaction. Therefore, this study tested the mediating effect of the nurse-patient relationship between emotional labor and job satisfaction among Chinese nurses. A total of 496 nurses were included in the study. Data collection was from December 2021 to March 2022 using the convenience sampling method. SPSS 26.0 and AMOS 23.0 software were used to perform structural equation modeling and analyze the relationship between variables. The results showed surface acting negatively affected nurse-patient relationships and job satisfaction, contrary to deep acting and naturally felt emotions. The parallel mediation of nurse-patient trust and patient-centered nursing in the relationship between emotional labor and job satisfaction was found to be statistically significant. Our study highlighted the important mediation of nurse-patient trust and the importance of the positive effects of emotional labor. Future studies can use these findings as a reference to develop interventions.